2017
DOI: 10.18805/ijar.b-3302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preovulatory follicle on fertility in Graded murrah buffaloes (Bubalus bubalis)

Abstract: An investigation was taken up to study the relationship of preovulatory follicle size at the time of first postpartum AI and CL biometry with conception using transrectal ultrasonography in 70 parous Graded Murrah buffaloes maintained under rural conditions. POF sizes were measured ultrasonographically and grouped in to small preovulatory follicle (SPF), medium preovulatory follicle (MPF) and large preovulatory follicle (LPF). Serum progesterone concentration at the time of AI and pregnancy status was negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…When POF size was grouped based on the parity, the POF size was found to be nonsignificantly smaller (12.97 ± 0.27 mm) in heifers than parous (13.25 ± 0.22mm) buffaloes in present study which is in agreement with Raj et al, (2018) who also reported larger follicle size in pluriparous buffaloes (15.3 mm) than the primiparous (15.07 mm). Tenhagen et al, (2003) sighted that follicle size is affected by parity, with primiparous cattle producing smaller follicles than pluriparous ones.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…When POF size was grouped based on the parity, the POF size was found to be nonsignificantly smaller (12.97 ± 0.27 mm) in heifers than parous (13.25 ± 0.22mm) buffaloes in present study which is in agreement with Raj et al, (2018) who also reported larger follicle size in pluriparous buffaloes (15.3 mm) than the primiparous (15.07 mm). Tenhagen et al, (2003) sighted that follicle size is affected by parity, with primiparous cattle producing smaller follicles than pluriparous ones.…”
Section: Resultssupporting
confidence: 90%
“…It has been documented that with increasing POF size, conception rate decreases in cows (Lynch et al, 2010, Vasconcelos et al, 1999. On the contrary, studies have reported that larger POF contributed to higher pregnancy rates (Raj et al, 2018 andPandey et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some components, which are known to influence oocyte maturation and/or embryo development are affected by follicular growth and development and/or by level of nutrition, whereas others are still need further investigation (Fig 1). Therefore, the trials to improve culture conditions (Mohammed 2006;Mohammed 2008;Lee et al, 2018) for in vitro embryo production (IVP) are still required as quality of oocytes (Mohammed 2017;Mohammed and Al-Hozab, 2018;Maylinda et al, 2018;Raj et al, 2018).…”
mentioning
confidence: 99%